1991
DOI: 10.1021/bi00111a011
|View full text |Cite
|
Sign up to set email alerts
|

Determination of rates and yields of interchromophore (folate .fwdarw. flavin) energy transfer and intermolecular (flavin .fwdarw. DNA) electron transfer in Escherichia coli photolyase by time-resolved fluorescence and absorption spectroscopy

Abstract: Escherichia coli DNA photolyase, which photorepairs cyclobutane pyrimidine dimers, contains two chromophore cofactors, 1,5-dihydroflavin adenine dinucleotide (FADH2) and 5,10-methenyltetrahydrofolate (MTHF). Previous work has shown that MTHF is the primary photoreceptor which transfers energy to the FADH2 cofactor; the FADH2 singlet excited state then repairs the photodimer by electron transfer. In this study, we have determined the rate constants for these photophysical processes by time-resolved fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
126
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 36 publications
10
126
1
Order By: Relevance
“…All known photolyases contain a reduced f lavin-adenine dinucleotide (FADH 2 ) as a catalytic cofactor. It has been shown in experiments with other CPD photolyases that the pyrimidine-dimer is repaired by electron transfer from FADH 2 (4,5). Class I photolyases are classified according to their second chromophore into either a deazaflavin-or folate-type.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All known photolyases contain a reduced f lavin-adenine dinucleotide (FADH 2 ) as a catalytic cofactor. It has been shown in experiments with other CPD photolyases that the pyrimidine-dimer is repaired by electron transfer from FADH 2 (4,5). Class I photolyases are classified according to their second chromophore into either a deazaflavin-or folate-type.…”
mentioning
confidence: 99%
“…They are the first three-dimensional structures for each type of photolyase, in which the geometry of the two cofactors became clear and an analysis of the energy-transfer process was made. Both types of photolyases have a similar backbone structure of the apoprotein, but show completely different binding modes for the lightharvesting cofactors, which account for the more efficient energy transfer in A. nidulans photolyase than in E. coli photolyase (4,5,7). For the substrate recognition, the base-flipping mechanism was proposed on the basis of the structure of E. coli photolyase (6).…”
mentioning
confidence: 99%
“…Photolyase binds specifically to damaged DNA. After complex formation, the repair reaction is presumably initiated by electron transfer from photoexcited FADH Ϫ to the pyrimidine dimer (17).…”
mentioning
confidence: 99%
“…Ultrafast spectroscopic studies have recently been reported in several flavin enzymes (12)(13)(14)(15)(16). The fluorescence quenching of both RfBP and GOX was observed to occur on femtosecond and picosecond time scales by measurements of the excited-state flavin (RF* or FAD*) fluorescence decay (16).…”
mentioning
confidence: 99%